Joint IFS/ILCA workshop on small ruminant research in the tropics - International Foundation for Science (IFS, 1984)
Reports presentations to a small ruminant research workshop that dealt with productivity, nutrition, reproduction & pathology of small ruminants, with particular reference to conditions in Africa.